Expressão dos genes BDNF, C3, GPx e CAT em um modelo animal de neurodegeneração após tratamento com extrato bruto do fruto de Vaccinium myrtillus L., ericaceae - Belache, Fernanda de Noronha Sertori (2018)
Alzheimer's disease (AD) is the leading age-related neurodegenerative disease. AD is characterized by neurofibrillary formation arising from Tau protein hyperphosphorylation and the formation of senile plaques by a β-amyloid protein tumor. The model of neurodegeneration with intracerebroventricular injection (icv) of streptozotocin (STZ) is used to study sporadic AD (AED). Drug intoxication is not free, as a consequence, oxidative stress and neuroinflammation. Plant sources with antioxidant properties have been prominent in works related to the development of alternative therapies for a disease. Phenolic compounds present in some species and biological activities antioxidant and antiinflammatory, and may help in reducing brain damage and cognitive impairment observed in AED. The objective of the present study was to evaluate the effect of the crude extract of the fruits of Vaccinium myrtillus L. on the expression of genes that perform functions in the neurogenesis, oxidative and neuroinflammatory processes in an animal model of neurodegeneration induced by the icv administration of STZ. Twenty male Wistar rats were divided into four experimental groups, with the same number of animals in each group (n = 5): group 1, control group, in which the animals received citrate buffer via icv and oral distilled water; group 2 who received STZ injection by icv and oral distilled water; group 3, group that received STZ by icv and were treated with the crude extract of the V. myrtillus fruit orally at the concentration of 200 mg/kg; and group 4 composed of animals that received STZ by icv and were treated with the oral extract at a concentration of 400 mg/kg. The experiment was conducted for 30 days. Behavioral tests were then performed for two months. After these tests, the euthanasia of the animals and the removal of the encephalon were made for hippocampal dissection and RNA extraction. Total tissue RNA was extracted with the Trizol™ Reagent extraction kit in combination with the PureLink® RNA Mini Kit (Life Technologies), converted into complementary DNA (cDNA) by the reverse transcription reaction. Samples were submitted to quantitative polymerase chain reaction (RT-qPCR) for relative quantification of brain-derived neurotrophic factor (BDNF), complement system C3, glutathione peroxidase (GPx) and catalase (CAT) genes. Analyzes showed that there was no significant difference in the expression of BDNF, GPx and CAT genes between the animals that received STZ icv and the control group after two months of treatment with crude extract. There was a significant difference in expression of C3 in the groups that received icv administration of STZ. This result demonstrates the existence of an inflammatory process associated with STZ injection. However, no difference in expression was observed between the groups that received STZ administration and were submitted to treatment with aqueous extract of V. myrtillus fruit, showing that the extract does not influence the regulation of the expression of this gene.